SG_C-Projective, Injective and Flat modules - Parimala M; Udhayakumar Ramalingam (Journal of the Indonesian Mathematical Society, 2019)
In this paper we introduce the concepts of $SG_C$-projective, injective and flat modules, where $C$ is a semidualizing module and we discuss some connections among $SG_C$-projective, injective and flat modules.